2015
DOI: 10.1007/s13753-015-0067-0
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Footprint of Transitional Shelters

Abstract: Extreme weather events, sea level rise, and political disputes linked to climate change are driving masses to leave their homes. Their transitional settlements should be produced in a manner that causes minimum greenhouse gas (GHG) emissions to prevent any further acceleration of climate change and the humanitarian crises it causes. This article presents a study of the carbon footprint and primary energy demand of the construction materials of eight different transitional shelters. The lowest carbon footprints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…In regard to the carbon storage of bamboo-based construction, the number of studies is clearly smaller than the number of similar studies for wood-based construction products. The climate impact studies of bamboo construction include reports on the carbon footprint of bamboo wall panels (Ramirez et al 2014), bamboo flooring (Gu et al 2019), bamboo scaffoldings (Laleicke et al 2015), or humanitarian emergency shelters made from bamboo (Kuittinen and Winter 2015). We rank the TRL of bamboo as 9, due to its wide commercial and vernacular use in construction.…”
Section: Other Bio-based Construction Materialsmentioning
confidence: 99%
“…In regard to the carbon storage of bamboo-based construction, the number of studies is clearly smaller than the number of similar studies for wood-based construction products. The climate impact studies of bamboo construction include reports on the carbon footprint of bamboo wall panels (Ramirez et al 2014), bamboo flooring (Gu et al 2019), bamboo scaffoldings (Laleicke et al 2015), or humanitarian emergency shelters made from bamboo (Kuittinen and Winter 2015). We rank the TRL of bamboo as 9, due to its wide commercial and vernacular use in construction.…”
Section: Other Bio-based Construction Materialsmentioning
confidence: 99%
“…Temporary shelters normally consume substantial amounts of energy and use a wide range of resources during the energy-intensive construction and building processfrom raw material extraction and production to construction and operation, all the way to the end of a shelter's life and its consequent disposal (Obyn et al, 2015;Dabaieh, 2017a). Normally, temporary refugee housing is built to last one or two decades at most, but sometimes shelters are demolished after only two or three years, leaving behind various environmental burdens after demolition plus a high carbon footprint due to its short life span (Atmaca, 2018;Kuittinen and Winter, 2015). Using natural materials in temporary shelter construction results in low impact shelters and can be one way of reducing the negative environmental impacts accrued from construction and demolition (Dabaieh, 2017a;Kuittinen and Winter, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Normally, temporary refugee housing is built to last one or two decades at most, but sometimes shelters are demolished after only two or three years, leaving behind various environmental burdens after demolition plus a high carbon footprint due to its short life span (Atmaca, 2018;Kuittinen and Winter, 2015). Using natural materials in temporary shelter construction results in low impact shelters and can be one way of reducing the negative environmental impacts accrued from construction and demolition (Dabaieh, 2017a;Kuittinen and Winter, 2015). In addition, building shelters with natural materials and passive systems for heating, cooling and ventilation can effectively reduce carbon emissions and energy consumption while they are in use (Dabaieh, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Kuittinen and Winter (2015) studied the carbon footprint of eight transitional shelters by the International Federation of Red Cross and Red Crescent Societies (IFRC) and compared the emissions to their construction costs. They concluded that construction materials can make a remarkable difference to the carbon footprint during the production phase of the shelters.…”
Section: Introductionmentioning
confidence: 99%